Apoptotic cell death induced by a mouse-human anti-APO-1 chimeric antibody leads to tumor regression - Coney, Leslie R.; Daniel, Peter T.; Sanborn, David; Dhein, Jens; Debatin, Klaus-Michael; Krammer, Peter H.; Zurawski Jr., V. R. (International journal of cancer, 1994)
The murine anti-APO-1 antibody (γ3, k) induces programmed cell death (apoptosis) following binding to the APO-I antigen (m.w., 48 kDa) expressed, e.g., on activated or malignant lymphocytes. APO-I expression on malignant cell lines and tissues suggested potential clinical utility supported by anti-APO-I-mediated tumor regression in a nude mouse model. A mouse-human anti-APO-1 chimeric antibody (γ3, k) with an affinity similar to that of the murine antibody was produced. Chimeric anti-APO-1 showed the same potential to inhibit growth of the SKW6.4 B-lymphoblastoid cell line as murine anti-APO-1, In addition, both the chimeric and murine anti-APO-1 antibodies were equally capable of mediating complete macroscopic tumor regression of a SKW6.4 xenotransplant in SCID mice by induction of apoptosis. Induction of apoptosis was the only mechanism for tumor regression because neither murine nor chimeric anti-APO-1 showed anti-tumor activity against solid H53 tumor (APO-1 antigen-positive, anti-APO-1 -resistant) xenotransplants. Our results indicate that the chimeric anti-APO-1 antibody effectively induces apoptosis and suggest that chimeric anti-APO-1 should be evaluated for the treatment of malignant cells expressing the APO-1 antigen. However, chimeric anti-APO-1 might only be used therapeutically when the antibody can be targeted specifically to tumor cells.
Gesehen am 24.09.2024